Practical studies of brand management based on the factor of consumer values - CHEN, Ke (Institutional Knowledge at Singapore Management University, 2021)
2021 will be the final year of the centenary goal of “building a moderately prosperous society in all respects”. Looking back over the past century, China has not only witnessed an increase in national income, but also ushered in abundant changes in social culture and people's spiritual world, and completed the transformation from a traditional single homogeneous cultural society to a flexible and diverse heterogeneous cultural society. In this process, brands become the product of values change and multicultural shock, and consumers shop not only to meet the needs of material functions, but also to express their personal values. To establish an effective relationship with consumers, brands must understand their value demands. However, traditional brand research rarely focuses on the fact that brands are the product of changing consumer values, and consumer research is mostly limited to the rational level. This leads to the questions: what is the role of consumers' perceptual values for brands? Is there a method to quantify and apply the intangible perceptual values? Is there a way to study and guide the application of intangible perceptual values in a quantitative way? To solve the above questions, we adopt abductive reasoning method to explore the following points: first, we put forward the core hypothesis -- consumers' perceptual value has a positive impact on brand development, and CVBBM (Customer-values-based Brand Management) is an effective perceptual value research tool. CVBBM is an original consumer research tool that helps brands identify their core consumer groups and their perceptual value points. Based on the brand management practice of a certain brand, we elaborate on the theoretical basis, operation process, output results and landing guidance of CVBBM. Further, to evaluate the impact of perceptual value on brand development and verify the effectiveness of CVBBM tool, we use fuzzy-set qualitative comparative analysis (fsQCA) to explore the impact of perceptual value and other conditions and their combinations on brand performance growth. Finally, we’ve found that: 1) brand development is not the result of a single point of force, but the product of the interaction of multiple factors, and no single variable can constitute a sufficient and necessary condition for brand performance improvement; 2) there are a variety of success paths for brands, but consumers' perceptual values are the overlap of these success paths and the necessary condition to drive performance improvement; 3) CVBBM can help brands define perceptual value, drive multi-dimensional practice optimization and performance improvement, and is an effective tool for perceptual value research.